Fish feeding technology - Toxirov, Baxtiyor Baxshilloyevich; Tag’aeva, Muhayo Bafoevna; To’murodova, Shoira Shavqat qizi (Science and Education, 2023)
The article examines ways of reproduction of zooplankton and phytoplankton organisms, which are the main food of fish, are found in artificial fisheries reservoirs.